2018
DOI: 10.3390/f9060290
|View full text |Cite
|
Sign up to set email alerts
|

Soil Chemical Attributes, Biometric Characteristics, and Concentrations of N and P in Leaves and Litter Affected by Fertilization and the Number of Sprouts per the Eucalyptus L’Hér. Strain in the Brazilian Cerrado

Abstract: Given the lack of recommendations for the fertilization of Eucalyptus clones in the second production cycle, the effects of fertilizer rates and the number of sprouts per strain in terms of the soil chemical attributes, biometric characteristics, and the concentrations of N and P in the leaves and in the litter of Eucalyptus L'Hér. in the Brazilian Cerrado were evaluated. The experimental design was a randomized block with four replicates, arranged in a 2 × 4 factorial scheme: one or two sprouts per strain; fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…However, we confirmed the substantial bidirectional transfer of N occurred between the litters using experiments under field conditions, which showed the net transfer of N from high-N to low-N litter [13]. This is consistent with results obtained by Godoi et al, in which it was found that the N leaf concentration correlated positively with the N in the Eucalyptus litter under field conditions [61]. This result suggested that transferred N in Eucalyptus (% Ndft) would be increased in the field due to the increase the absorption N from the leguminous plants' litter, while litter and microbes had smaller effects on N transfer in our experiment compared with those in natural and commercial areas [13,62].…”
Section: N Transfer Probably Occurs But Differs Between Natural Areas and Commercial Areassupporting
confidence: 93%
“…However, we confirmed the substantial bidirectional transfer of N occurred between the litters using experiments under field conditions, which showed the net transfer of N from high-N to low-N litter [13]. This is consistent with results obtained by Godoi et al, in which it was found that the N leaf concentration correlated positively with the N in the Eucalyptus litter under field conditions [61]. This result suggested that transferred N in Eucalyptus (% Ndft) would be increased in the field due to the increase the absorption N from the leguminous plants' litter, while litter and microbes had smaller effects on N transfer in our experiment compared with those in natural and commercial areas [13,62].…”
Section: N Transfer Probably Occurs But Differs Between Natural Areas and Commercial Areassupporting
confidence: 93%
“…Similarly, Godoi et al [7], in their research on the second production cycle of eucalyptus in the Brazilian Cerrado region, verified that mineral fertilization (doses of formula 06-30-06 + 1% Ca + 3% S + 1% Mg + 1.5% Cu + 1% Zn) affects the chemical attributes of the soils at depths of 0-1.00 m and largely provides higher P and B contents.…”
Section: Soil Chemical Analysismentioning
confidence: 78%
“…Fertilization of eucalyptus is one of the most important strategies that contributes 30-50% of the gains in wood productivity in forest sites [6]. It is also worth noting that approximately 86% of the eucalyptus wood volume in the second cycle can be obtained from the supply of soil and root nutrient reserves while 14% of productivity was obtained due to mineral fertilization [7]. Therefore, proper fertilization in the first cycle of eucalyptus can fulfill almost all the nutritional demands of the second production cycle in the Cerrado region.…”
Section: Introductionmentioning
confidence: 99%